2020
DOI: 10.36547/be.2020.3.4.74-76
|View full text |Cite
|
Sign up to set email alerts
|

Texturized Soy Protein as an Alternative Low-Cost Media for Bacteria Cultivation

Abstract: Most of the culture media used in bacterial growth is composed of complex ingredients, increasing the value of the product. This makes its acquisition unavailable by educational institutions without sufficient funding, making even more difficult the practical teaching of microbiology. Therefore, the development of an alternative medium of simple composition and low-cost becomes necessary. This work aimed to use texturized soy protein (TSP) as a low cost culture medium that allows the bacterial growth. For the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 9 publications
(10 reference statements)
1
6
0
Order By: Relevance
“…The work demonstrated the viability of an easily formulated, low cost, and highly efficient culture medium (Cruz et al, 2020).…”
Section: Alternative Culture Media For Microbial Growthmentioning
confidence: 92%
See 2 more Smart Citations
“…The work demonstrated the viability of an easily formulated, low cost, and highly efficient culture medium (Cruz et al, 2020).…”
Section: Alternative Culture Media For Microbial Growthmentioning
confidence: 92%
“…Agro-industrial waste has great diversity and has been shown to have potential for application in different areas, such as use as a source of fibers, polyphenols and bioactive compounds in general (Costa et al, 2020;Tagliani et al, 2019), organization and management of fruit and vegetable residues for human and animal consumption (Ramírez et al, 2020) and application in the development of alternative culture media (Cruz et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also predicted that a large number of bacteria species in the environment also cannot be cultured due to the lack of appropriate media which are needed for their growth [6]. This is the main driving force behind the constant effort for the formulation and development of newer media for bacterial culture [8][9][10]. Such new media will allow scientists to grow and study currently un-culturable bacterial species Plants are rich in a wide variety of chemical compounds such as tannins, terpenoids, alkaloids, and avonoids which have been found to possess antimicrobial properties against wide variety of bacterial pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…It is also predicted that a large number of bacteria species in the environment also cannot be cultured due to the lack of appropriate media which are needed for their growth [ 6 ]. This is the main driving force behind the constant effort for the formulation and development of newer media for culture of bacteria [ 8 – 10 ]. Such new media will allow scientists to grow and study currently un-culturable bacterial species.…”
Section: Introductionmentioning
confidence: 99%